Application of results of geological exploration of deposits of solid mineral raw materials in mining - Ilić Miloje M. (Tehnika, 2017)
Important application in mining have the results of geological exploration of the deposits of solid mineral raw materials, before all geological data obtained (including their interpretations) regarding basic properties of the deposts and their changeability, and regarding quantity and quality (i.e. resources and reserves) of the belonging mineral raw material which have an essential significance for mineral projects. The geological data, together with the other relevant data (in the first place technical and economic ones) are applied as basic parameters in documentation of mineral projects. Since the successfulness of the projects is dependent upon the confidence of the data, a special attention is dedicated to the acts that contribute to attaining of an adequate level of confidence of the data, as follows: a) a gradual realization of the projects through two phases (geological and mining ones) having seven development stages (reconnaissance, prospecting, preliminary exploration and detailed exploration stages of the geological phase and mine design, mine construction and mine production stages of the mining phase); b) finding out optimal solutions in drawing up a plan of exploratory workings and its carrying out in accordance with basic properties of a deposit and their changeability; c) a realistic estimation of mineral resources/reserves as a predominantly geological task (not 'calculation' of the resources/reserves as a mathematical task); d) an objective evaluation of the successfulness of a project at the end of every geological stage ‒ presented in corresponding geological analyses and technical-economic studies.